2005
DOI: 10.1523/jneurosci.4279-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of GD1a Ganglioside Sensitizes Motor Nerve Terminals to Anti-GD1a Antibody-Mediated Injury in a Model of Acute Motor Axonal Neuropathy

Abstract: Anti-GD1a ganglioside antibodies (Abs) are the serological hallmark of the acute motor axonal form of the post-infectious paralysis, Guillain-Barré syndrome. Development of a disease model in mice has been impeded by the weak immunogenicity of gangliosides and the apparent resistance of GD1a-containing neural membranes to anti-GD1a antibody-mediated injury. Here we used mice with altered ganglioside biosynthesis to generate such a model at motor nerve terminals. First, we bypassed immunological tolerance by im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(101 citation statements)
references
References 61 publications
6
92
0
2
Order By: Relevance
“…Importantly, no inflammatory or demyelinating lesions were noted in nervous tissue, which generally has the highest tissue expression of gangliosides (data not shown). Normal mice appear to be resistant to neural injury during anti-GD1a antibody exposure, demonstrating the central role of membrane antigen density in modulating both immune tolerance to GD1a and axonal susceptibility to anti-GD1a antibody mediated injury [37]. In keeping with these general concepts our histopathology studies suggest that CMPs do not induce antibodies that mediate normal tissue destruction targeting gangliosides due to their low density of expression.…”
Section: Cmps Induce Anti-tumor Responses With Absence Of Normal Tisssupporting
confidence: 65%
See 2 more Smart Citations
“…Importantly, no inflammatory or demyelinating lesions were noted in nervous tissue, which generally has the highest tissue expression of gangliosides (data not shown). Normal mice appear to be resistant to neural injury during anti-GD1a antibody exposure, demonstrating the central role of membrane antigen density in modulating both immune tolerance to GD1a and axonal susceptibility to anti-GD1a antibody mediated injury [37]. In keeping with these general concepts our histopathology studies suggest that CMPs do not induce antibodies that mediate normal tissue destruction targeting gangliosides due to their low density of expression.…”
Section: Cmps Induce Anti-tumor Responses With Absence Of Normal Tisssupporting
confidence: 65%
“…Our results indicate that a small increase in anti ssDNA is within normal variation, and is without clinical consequence in these mice. In pristane induced lupus ssDNA antibodies were found to be the first autoreactivity to appear (37), but appearance of these antibodies was followed within a couple of months by a diverse set of other pathological atuoreactivities. Thus, we hypothesize that the CMPs induced slightly increased levels of (natural) autoantibodies, but did not bring about overt autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brains of compound null-mutants have increased GM3 expression Kawai et al, 2001). Our previous studies on pathophysiological effects of anti-ganglioside antibodies suggest that similar ganglioside accumulations also take place at NMJ motor nerve terminals of these mutants (Bullens et al, 2002;Goodfellow et al, 2005). The exact time course of these ganglioside accumulations in brain and NMJ are not known.…”
Section: Introductionmentioning
confidence: 97%
“…Numerous investigators over several decades and several continents have attempted to determine whether these antibodies are pathogenetic and how they mediate damage. In summary, many collaborative efforts have demonstrated that anti-GM1 and anti-GQ1b antibodies bind to peripheral nerve and neuromuscular junctions 64,65 , and anti-GD1a antibodies bind to the nodes of Ranvier, paranodal myelin and neuromuscular junction 66,67,68 . Upon binding, the antibodies activate the complement cascade, resulting in formation of the membrane attack complex, disruption of sodium channel clusters at the node of Ranvier with disruption of nodal architecture 69 , and calcium influx and calpain-dependent neuronal and glial injury at the neuromuscular junction 70,71 .This injury can be ameliorated with complement inhibitors 72,73 .…”
mentioning
confidence: 99%